Preconsultation compassion intervention to reduce anxiety among patients referred to a cancer center: protocol for a randomised control trial. Issue 5 (24th May 2021) - Winn, Christine; Generosa, Grana; Mazzarelli, Anthony; Trzeciak, Stephen; Roberts, Brian W
Abstract : Introduction: Patients diagnosed with cancer commonly have a high degree of anxiety during an initial oncology consultation, which may interfere with a patient's ability to retain information required to make informed treatment decisions. A previous study randomised breast cancer survivors (volunteers) to view either (a) a brief video depicting a standard initial consultation from an oncologist or (b) an identical consultation with the addition of compassionate statements from the oncologist, and found the compassionate statements reduced anxiety among the volunteers. However, while compassionate statements reduced anxiety during simulation, it is currently unknown whether watching a video containing compassionate statements from an oncologist prior to an initial oncology consultation will reduce anxiety among patients referred to a cancer centre. The aim of this randomised control trial is to test whether watching a brief video containing compassionate statements from an oncologist, compared with watching a standard introduction video, prior to an initial oncology consultation will reduce the degree of anxiety among patients referred to a cancer centre. Methods and analysis: This is a prospective, randomised controlled clinical trial at an academic cancer centre. We will enrol adult patients scheduled for an initial oncology consultation. Subjects will be randomly assigned to receive a standard introduction video or enhanced compassion video for viewing prior to the initial oncology consultation. On arrival to the cancer centre, we will measure anxiety severity using the Hospital Anxiety and Depression Scale (HADS). The HADS has two 7-item subscales (HADS anxiety and HADS depression) and is well-validated among oncology patients. We will use Wilcoxon rank-sum test to test for a difference in the HADS subscales between the two video groups. Ethics and dissemination: The Cooper University Hospital Institutional Review Board approved this study. The results from this randomised control trial will be submitted for publication to a peer-reviewed journal. Trial registration number: NCT04503681 .